Cutaneous metastatic breast carcinoma - Mordenti, C... (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2000)
Background. Cancer metastasis represents the most devastating aspect of malignancy since mortality of tumor patients is mainly related to the metastatic behavior of the primary neoplasm. Excluding melanoma, the most common tumor to metastasize to the skin is breast cancer. Materials and Methods. We examined retrospectively the clinical, histopathologic and immunohistochemical features of 164 cases of skin metastases from breast carcinoma. Results. Clinical features included papules and/or nodules in 131 patients (80%), telangiectatic carcinoma in 19 (11.2%), erysipeloid carcinoma in 5 (3%), "en cuirasse" carcinoma in 5 (3%), alopecia neoplastica in 3 (2%) and a zosteriform pattern in 1 patient (0.8%). Sites of cutaneous metastases were the trunk (145), head and neck (14) and extremities (5). Histopathologic features of adenocarcinoma with varying degrees of cell differentiation were observed although distinctive findings were associated with each clinical pattern. Immunohistochemical studies showed a positive staining with anti-cytokeratin and anti-EMA antibodies whereas reactivity with anti-CEA was detected in 110 of 164 cases (67%). Conclusion. In conclusions, cutaneous metastatic breast carcinoma is characterized in most cases by suggestive clinical and histopathologic features and is usually associated with late stages of the disease.
Keywords: Breast neoplasms; Complications; dermatologija; Diagnosis; dojke; metastaze; Neoplasm metastasis; Pathology; rak (medicina); Secondary; Skin neoplasms